Facilitators and barriers to integration of noncommunicable diseases with HIV care at primary health care in Ethiopia: a qualitative analysis using CFIR - Badacho, Abebe Sorsa; Mahomed, Ozayr Haroon (Frontiers in Public Health, 2023)
The rise in non-communicable diseases (NCD), such as hypertension and diabetes among people living with human immunodeficiency virus (PLWH), has increased the demand for integrated care due to multiple chronic care needs. However, there is a dearth of evidence on contextual factors implementing integrated hypertension and diabetes care with HIV care. This study aimed to identify facilitators and barriers that could affect the integration of hypertension and diabetes with HIV care at primary health care in Ethiopia.Methods: Five primary health facilities from five districts of the Wolaita zone of South Ethiopia were included in the qualitative study. Fifteen key informant interviews were conducted with healthcare providers and managers from the Zonal, district, and facility levels from October to November 2022. Data collection and analysis were guided by a consolidated framework of implementation research (CFIR).Results: Ten CFIR constructs were found to influence the integration. Perceived benefit of integration to patients, healthcare providers, and organization; perceived possibilities of integration implementation; availability of NCD guidelines and strategies; a supportive policy of decentralization and integration; perceived leaders and healthcare provider commitment were found to be facilitators. Perceived increased cost, insufficient attention to NCD care needs, inadequate number of trained professionals, inadequate equipment and apparatus such as blood pressure measurement, glucometers, strips, and NCD drugs, inadequate allocation of budget and weak health financing system and poor culture of data capturing and reporting were identified as barriers to integration.It is important to address contextual barriers through innovative implementation science solutions to address multiple chronic care needs of PLWH by implementing integrated hypertension and diabetes with HIV care in primary healthcare. Training and task shifting, pairing experienced professionals, and strengthening the health care financing system to implement evidence-based integration of hypertension and diabetes are recommended.